**Weegy:** 5(x + 1) = 4(x + 8) 5x + 5 = 4x + 32 5x - 4x = 32 - 5 x = 27

**User:**
Solve for x.
3(x + 2) + 4(x - 5) = 10
x = 36/7
x = 24/7
x = 16/7
x = 9/7

**User:**
Simplify the given equation.
6 - (3x + 10) + 4(2 - x) = 15
4 - 7x = 15
4 - 4x = 15
12 - 7x = 15

**User:**
Simplify the given equation.
5x + 2(x - 3) = -2(x - 1)
7x - 6 = -2x - 2
7x - 6 = -2x + 2
7x - 3 = -2x - 1

**Weegy:** 5x + 2(x - 3) = -2(x - 1) 5x + 2x - 6 = -2x + 2 7x - 6 = -2x + 2 which is the simplified form.

**User:**
Solve for x.
8(x + 1) - 3(x + 4) = 7(2 - x)
x = -1
x = -1
x = 1
x = 1

**User:**
Solve for x.
5(x - 3) + 4(x + 3) = 3(x - 1)
x = 0
x = 1/4
x = 1/2
x = 1

**User:**
Solve for x.
7(x + 2) = 6(x + 5)
x = -44
x = -16
x = 16
x = 44

**User:**
Solve for x.
7(3 - x) = 8(4 - 2x)
x = -53/23
x = -5/9
x = 11/23
x = 11/9

**Weegy:** 7(3 - x) = 8(4 - 2x) 21 - 7x = 32 - 16x -7x + 16x = 32 - 21 9x = 11 x = 11/9

**User:**
Solve for x.
7(x - 3) + 3(4 - x) = -8
x = 1/4
x = 25/10
x = -16/19
x = -41/10

**Weegy:**
7(x - 3) + 3(4 - x) = -8
7x - 21 + 12 - 3x = -8
4x - 9 = -8
4x = -8 + 9
4x = 1
x = 1/4

(More)8

3(x + 2) + 4(x - 5) = 10

3x + 6 + 4x - 20 = 10

7x - 14 = 10

7x = 24

x = 24/7

Added 6/16/2015 6:53:35 PM

This answer has been confirmed as correct and helpful.

Confirmed by

Andrew. [6/17/2015 3:21:35 AM]

8

6 - (3x + 10) + 4(2 - x) = 15

6 - 3x - 10 + 8 - 4x = 15

-7x + 4 = 15

4 -7x = 15

The answer is 4 - 7x = 15 .

Added 6/16/2015 6:55:56 PM

This answer has been confirmed as correct and helpful.

Confirmed by

Andrew. [6/17/2015 3:22:40 AM]

8

8(x + 1) - 3(x + 4) = 7(2 - x)

8x + 8 - 3x - 12 = 14 - 7x

5x - 4 = 14 - 7x

5x + 7x = 14 + 4

12x = 18

x = 18/12

x = 3/2

Added 6/16/2015 6:57:21 PM

This answer has been confirmed as correct and helpful.

Confirmed by

Andrew. [6/17/2015 3:23:26 AM]

8

5(x - 3) + 4(x + 3) = 3(x - 1)

5x - 15 + 4x + 12 = 3x - 3

9x - 3 = 3x - 3

9x - 3x =-3 + 3

6x = 0

x = 0

Added 6/16/2015 6:59:50 PM

This answer has been confirmed as correct and helpful.

Confirmed by

Andrew. [6/17/2015 3:24:12 AM]

8

7(x + 2) = 6(x + 5)

7x + 14 = 6x + 30

7x - 6x = 30 - 14

x = 16

Added 6/16/2015 7:00:39 PM

This answer has been confirmed as correct and helpful.

Confirmed by

Andrew. [6/17/2015 3:24:34 AM]